Keefektifan Konseling Kelompok Rational Emotive Behavioral Therapy untuk meningkatkan Forgiveness siswa - Luthfinuddin, Hafiski; Permatasari, Devi; Rahmawati, Ajeng Intan Nur (Syifaul Qulub: Jurnal Bimbingan dan Konseling Islam, 2024)
The purpose of this research is to determine the effectiveness of Rational Emotive Behavior Therapy group counseling to increase students' Forgiveness. The research design uses Non-Equivalent Control Group Design with Experimental and Control Groups. The sampling technique uses Purposive Sampling with sample criteria that have a low category Forgiveness Score. The scale used is the Heartland Forgiveness Scale (HFS18) which has a validity of r up to 0.569 and reliability Î± = 0.830. Research results show that Rational Emotive Behavior Therapy group counseling is effective in increasing students' Forgiveness. Apart from that, there are variables belief (belief), emotion regulation (emotion regulation), and self-disclosure (self-disclosure) which influence students' level of forgiveness. The conclusion of this research shows that providing group counseling using the Rational Emotive Behavior Therapy approach is effective in increasing student forgiveness. Suggestions for future researchers are to involve the variables belief (belief), emotion regulation (emotion regulation), and self-disclosure which influence student forgiveness.